Analisa dan Perancangan Sistem Informasi Service Control Board System pada PT. XYZ berbasis Web - Makin, Samsul; Supiana, Nana; Kurniawan, Muhammad Arif (Universitas Insan Pembangunan Indonesia, 2023)
The service control board is a tool used to monitor workshop conditions according to actual conditions. there is a difference in the status of the service unit on the service control board manual with the actual service unit status in the workshop, the distance between the foreman''s office and the service advisor''s office is quite far so the foreman has to come to the service registration office every time to update the service unit''s status on the service control board manual, the customer has difficulty in read the service control board manual because it uses certain symbols. The service control board system information system is a solution to solve existing problems. With the creation of a service control board system, the processes and procedures for updating service unit status will be more effective and efficient and the information displayed will be more accurate and real-time.